2015
DOI: 10.1177/1087057115570550
|View full text |Cite
|
Sign up to set email alerts
|

A Fragment-Based Ligand Screen Against Part of a Large Protein Machine: The ND1 Domains of the AAA+ ATPase p97/VCP

Abstract: The ubiquitous AAA+ ATPase p97 functions as a dynamic molecular machine driving several cellular processes. It is essential in regulating protein homeostasis, and it represents a potential drug target for cancer, particularly when there is a greater reliance on the endoplasmic reticulum-associated protein degradation pathway and ubiquitin-proteasome pathway to degrade an overabundance of secreted proteins. Here, we report a case study for using fragment-based ligand design approaches against this large and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 32 publications
9
27
0
Order By: Relevance
“…The affinity (Kd) of ADP to p97-ND1 was measured to be 200 ± 14 nM using a Langmuir model based on steady state measurements of a dilution series. This value is in agreement with reported affinities for ND1 constructs of similar lengths; e.g., a value of 200 nM was reported for an ND1 fragment spanning amino acids 1-458, and a value of 98 nM for an ND1 fragment spanning amino acids 1-480 [26,29]. The kinetic analysis of the sensorgrams indicated a clear 1:1 binding model for ADP.…”
Section: Initial Biolayer Interferometry Screeningssupporting
confidence: 91%
See 1 more Smart Citation
“…The affinity (Kd) of ADP to p97-ND1 was measured to be 200 ± 14 nM using a Langmuir model based on steady state measurements of a dilution series. This value is in agreement with reported affinities for ND1 constructs of similar lengths; e.g., a value of 200 nM was reported for an ND1 fragment spanning amino acids 1-458, and a value of 98 nM for an ND1 fragment spanning amino acids 1-480 [26,29]. The kinetic analysis of the sensorgrams indicated a clear 1:1 binding model for ADP.…”
Section: Initial Biolayer Interferometry Screeningssupporting
confidence: 91%
“…The remaining fragments showed maximum STD-effects in a range from 10.5% (TROLL9) up to 72.5% (TROLL6). Similar results were obtained in the previously reported fragment screen with p97 [26]. An overview of the STD-effects is shown in Fig.…”
Section: Confirmation Of Selected Fragments By Std-nmrsupporting
confidence: 90%
“…Several classes of inhibitors, including those that act in an allosteric or competitive manner, have been identified that impair p97 ATPase activity (1014, 2127). Determination of the cryo-EM structure at 2.3 Å resolution of p97 in complex with UPCDC30245, a phenyl indole derivative (fig.…”
mentioning
confidence: 99%
“…To explore the multiple binding site on p97 and its dynamics further, a 2485‐member fragment library was screened by surface plasmon resonance (SPR), followed by NMR spectroscopy, to identify fragments that bound to the D1 or N domain of p97 . Even though this strategy is less high‐throughput than previously mentioned assays, it is useful in identifying fragments for studying p97’s dynamic nature, and the results could be usable for further lead optimization of future inhibitors.…”
Section: Small‐molecule Inhibitors Of 19s Rp Subunitsmentioning
confidence: 99%